Antioxidant and anti-obesity properties of selected local chili varieties in vitro - Chan, Suk Huei (2019)
Obesity is a complex metabolic disease caused by positive energy balance, which leads to an increase in body fat mass. Currently, obesity is a health concern as it may initiate common chronic diseases. Among Malaysians, almost half of the population is overweight or obese. Chili pepper is an important spice that brings spiciness and commonly used in Malaysian cuisines. In the previous studies conducted, chili pepper has been reported to have strong antioxidant and anti-obesity properties. However, the antioxidant and anti-obesity properties of chili varieties in Malaysia has not yet been fully investigated. This study was carried out to determine antioxidant properties (content and activity) and anti-obesity properties among chili pepper varieties in Malaysia. In the current study, seed, pulp, and whole fruit parts were separated from five different common varieties of chili peppers in Malaysia (Cili Kulai 151, Cili Kulai 568, Cili Bara, Cili Centil, and Cili Pelita). The total phenolic content (TPC) and total flavonoid content (TFC) of all ethanolic extracts of chili peppers were determined. The antioxidant activities of the extracts were determined through Ferric-Reducing Antioxidant Power (FRAP) and 2,2’azinobis-(3-ethyl-benzothiazoline-6-sulphonic acid (ABTS) assays. The extracts with the highest antioxidant activity from each part of chili (seed, pulp, whole fruit) undergone HPLC analysis for quantification of capsaicin. Cell cytotoxicity of the selected chili extracts was determined in 3T3-L1 preadipocytes using MTT assay. Whereas the ability to inhibit oil accumulation in fully differentiated 3T3-L1 adipocytes of the selected chili pepper extracts was assayed using Oil Red O staining. Inhibition of pancreatic lipase activity was determined spectrometrically. The results showed that Kulai 568 pulp extract had the highest level of TPC (47.88±0.220 mg GEA/g), whereas Centil pulp extract had the highest level of TFC (26.60±0.52 mg QE/g). In term of antioxidant activities, Bara pulp extract had the highest value in FRAP (3.058±0.002mM Fe²⁺/mg extract) and ABTS (IC₅₀ = 12.411±0.025) assays. The level of antioxidant content is strongly and positively correlated with antioxidant activities. Through HPLC analysis, Bara pulp extract showed the highest level of capsaicin (72.271±0.957µg/ml). Through MTT assay, the results showed the treatment time and dose- dependent properties of the chili extracts. Centil seed extract presented the best result in terms of inhibition of oil accumulation (69.09 – 92.20%), whereas Bara pulp extract inhibited the most pancreatic lipase activity (IC₅₀= 4.84±0.57µg/ml). Thus, it is suggested that Centil seed and Bara pulp extracts can be a potent antioxidant and anti-obesit ts for prevention of chronic diseases caused by free radicals and obesity treatment.